2005
DOI: 10.1074/jbc.c400573200
|View full text |Cite
|
Sign up to set email alerts
|

The Elasticity of Individual Titin PEVK Exons Measured by Single Molecule Atomic Force Microscopy

Abstract: The I-band region of the giant muscle protein titin contains a large domain enriched for the amino acids proline, glutamate, valine, and lysine and is denoted the PEVK domain. The PEVK domain of titin encodes a random coil shown to be an important factor in the passive elasticity of titin. Muscle-specific splicing of 116 PEVK exons encodes this domain. It has been proposed that proline contents determine the elasticity of the PEVK polypeptide, where the individual exons code for "flexibility cassettes." To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
6
42
0
1
Order By: Relevance
“…Although Ottenheijm et al demonstrated that the content of titin in COPD diaphragm was not different to non-COPD diaphragm, they found that there was an upregulation of gene expression in the titin molecule and postulated that this might be due to alternative splicing of the titin gene, resulting in a longer molecule. This ability of the titin molecule to lengthen, specifically through alternative splicing in the proline, glutamate, valine, and lysine (PEVK) region of the gene, has been previously demonstrated by Sarkar et al (30). The results of the present study, therefore, provide an important independent confirmation of Ottenheijm et al's (25) findings specifically that, when stretched, the reduction in passive tension generated in COPD diaphragm probably occurs through an elongation of the titin molecule.…”
Section: Discussionsupporting
confidence: 81%
“…Although Ottenheijm et al demonstrated that the content of titin in COPD diaphragm was not different to non-COPD diaphragm, they found that there was an upregulation of gene expression in the titin molecule and postulated that this might be due to alternative splicing of the titin gene, resulting in a longer molecule. This ability of the titin molecule to lengthen, specifically through alternative splicing in the proline, glutamate, valine, and lysine (PEVK) region of the gene, has been previously demonstrated by Sarkar et al (30). The results of the present study, therefore, provide an important independent confirmation of Ottenheijm et al's (25) findings specifically that, when stretched, the reduction in passive tension generated in COPD diaphragm probably occurs through an elongation of the titin molecule.…”
Section: Discussionsupporting
confidence: 81%
“…High-persistence-length values were also recently observed in chemically denatured proteins using FRET techniques (37). Such high-persistence lengths have also been observed in PEVK proteins (38)(39)(40) and considered to be an indication that, in addition to entropy, intramolecular interactions also play a role in the force-extension behavior of this natively disordered muscle protein (41,42). Thus, it is now clear that the apparent persistence length of Ϸ0.4 nm, resulting from WLC fits to protein unfolding data from atomic force microscopy experiments (43), reflected a phenomenological stiffness, comprising effects due to both chain entropy and hydrophobic collapse.…”
Section: Resultsmentioning
confidence: 52%
“…Polyproteins of ubiquitin, I27 and the PEVK-I27 chimera were cloned and expressed as described elsewhere (20,39,45). The PEVK-I27 construct is based on the human titin I27 and PEVK (exon 161) sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Those studies of intact titin and the Ig/Fn3 domains have provided a deeper understanding of how the elasticity of titin is adjusted by the sequential unfolding of Ig/Fn3 domains and how its elasticity recovers after domain refolding (Kellermayer et al, 1997;Rief et al, 1997;Carrion-Vazquez et al, 2000). More recently, the mechanical properties of expressed PEVK fragments based on cardiac and soleus PEVK exons were reported Linke et al, 2002;Watanabe et al, 2002;Labeit et al, 2003;Sarkar et al, 2005). Each study observed an unexpectedly broad distribution in the measured elastic persistence length of the PEVK segment.…”
Section: Introductionmentioning
confidence: 99%